Pengaruh Outcome Quality dan Peer To Peer Quality Terhadap Kepuasan Pasien Rawat Inap di RSI Ibnu Sina Payakumbuh - Dessy Angraini; Erlinengsih Erlinengsih; Regi Sariningsih (Yayasan Literasi Sains Indonesia, 2023)
The rapid growth of hospitals will lead to competition between hospitals. Hospital will compete to increase their competitiveness to gain and maintain its market. Based on the results of an initial survey of 6 out of 10 ipatents of the islamic hospital Ibnu Sina Payakumbuh, understand what is being debated at the hospital today is the outcome quality, whice include service quality problem where the nurse did not do check ups sistematically and effectivelly, and doctor who did not come to visit on time. And there are 5 out of 10 patients at Ibnu Sina Hospital Payakumbuh who said that about peer to peer quality needed is communication between patients in the room, the information obtained is less effective, and the benefits that can be lacking. This research is a quantitative study with cross sectional design using primary data and secondary data. The sample collection technique used is the proportional statified random sampling technique. The results showed no influence on outcame quality on patient satisfaction. And there is a significant relation between peer to peer quality and patient satisfaction. The conclusion of this study is the outcome quality has no influence on patient satisfaction. Peer to peer quality affects patient satisfaction. The suggestion from this study is that the hospital must pay attention to the positive correlation of outcome quality and it is recommended that the hospital maintain peer to peer quality for patients, and further researchers are expected to increase the number of research samples and more detailed questionnaire questions.